A literature review of critical thinking in engineering education. Issue 5 (4th May 2019) - Ahern, Aoife; Dominguez, Caroline; McNally, Ciaran; O'Sullivan, John J.; Pedrosa, Daniela
ABSTRACT: Developing optimum solutions to engineering problems typically relies on structured and complex thought processes that require evaluation, interpretation and opinion. Well-developed critical thinking (CT) skills are essential for dealing with the multi-dimensional nature of these problems. CT in an engineering context is well reported in teaching and learning academic literature. However, much of this is framed within theoretical and conceptual frameworks. Practical approaches of how CT skills are best promoted in engineering curricula are less common. A state-of-art review of practical interventions that target the development of CT in engineering students is presented. The review draws on 25 selected peer-reviewed journal articles in established engineering databases and focusses on teaching strategies where their effects in promoting CT skills in students are measured. Considerable variability in the reviewed literature was apparent. CT interventions and strategies are often reported, but metrics of their success in enhancing students' CT is often limited to qualitative, subjective inferences. To more robustly and holistically ensure that CT is clearly embedded in university curricula, there needs to be well-funded research programmes that allow different methods to be developed and trialled over extended periods in higher education engineering programmes.